Anisotropic 3D delay-damage model to simulate concrete structures - Gatuingt, Fabrice; Desmorat, Rodrigue; Chambart, Marion; Combescure, Didier; Guilbaud, Daniel (European Journal of Computational Mechanics, 2008)
Dynamic loadings lead to material degradation and structural failure. This is even more the case for concrete structures where the parts initially in compression break in tension due to waves propagation and reflection. The dissymmetry (mainly due to damage induced anisotropy) of the material behavior plays a major role in such cases. Loading induced damage is often anisotropic and one proposes here to take advantage of such a feature to build a damage model for concrete, dissymmetric in tension and in compression, 3D, suitable for dynamic computations. A single 2nd order tensorial damage variable D is considered with a damage law ensuring a damage rate proportional to the square of the positive part of the strain tensor. One focus in the present work on viscous regularizations for the anisotropic damage model proposed. Numerical examples illustrate the efficiency of the model to deal with 3D structures.